Short humeral stem in total shoulder arthroplasty does not jeopardize primary implant stability - Giulia Galteri, MSc; Sara Montanari, PhD; Giacomo Dozza, BSc; Marco Palanca, PhD; Luca Cristofolini, PhD (JSES International)
Background: The trend of the modern humeral components in total shoulder arthroplasty is toward shorter and shorter humeral stems. However, the question remains whether short uncemented stems can provide the same implant stability as long stems. This study aimed to evaluate and compare the torsional primary stability and the pull-out extraction force of both a long and a short version of the same stem. Materials and methods: Ten humeral components (five long stems and five short stems) were press-fitted into ten synthetic composite humeri. A torsional load was applied to generate the most critical loading condition. The specimens were loaded with 100 cycles between 2 Nm and 10 Nm, at 1 Hz. A 3D Digital Image Correlation system was used to measure the relative displacement between the prosthesis and the host bone during the test. After completing the torsional test, the pull-out force was measured. Differences between the long and short stem on the biomechanical parameters (permanent migrations, inducible micromotion, and extraction force) were tested with the nonparametric Mann-Whitney test (P < .05). Results: The main rotational inducible micromotion was around the craniocaudal axis. No significant differences were found between the rotational permanent migrations of the long and short stem around the craniocaudal (P = .421), anteroposterior (P = .841), and mediolateral axes (P = .452). No significant differences were found between the rotational inducible micromotions of the long and short stem around the craniocaudal (P = .222), anteroposterior (P = .420), and mediolateral axes (P = .655). No significant differences were found between the permanent translations of the long and short stem along the craniocaudal (P = .341), anteroposterior (P = .420), and mediolateral (P = .429) directions. No significant differences were found between the translations of the long and short stem in terms of inducible translation in the craniocaudal (P = .547), anteroposterior (P = .999), and mediolateral axes (P = .285). Similar extraction force (P = .35) was found. Discussion and Conclusion: No statistically significant difference was found between the long-stem and short-stem implants. These results show that short uncemented stems can provide adequate primary mechanical stability. As the long-stem version of this stem is already clinically used, the present findings suggest that the short version can be reasonably expected to deliver similar outcomes in terms of implant stability.